Effects of magnetic field inclination on tilted square cavity filled with a nanofluid saturated porous medium. Issue 4 (12th March 2021) - Sureshkumar, S.; Muthukumar, S.; Doh, Deog Hee; Prem, Eswari
ABSTRACT: The inclination effects of magnetic field on mixed convection in an inclined two-dimensional lid-driven square cavity filled with a nanofluid-saturated porous medium are investigated numerically. The bottom wall of the cavity is heated uniformly. The top wall is maintained with a constant cold temperature and it moves either in the positive or in the negative direction. The vertical sidewalls of the cavity are perfectly insulated. The finite volume method is used to solve the governing equations on a uniform staggered grid. The obtained results illustrate that the overall heat transfer rate increases with the increase of the inclination angles of magnetic field for both directions of lid movement. The inclination effects of cavity and the magnetic field are dominated by the low permeability of the porous medium. Regardless of the inclinations of the cavity and the magnetic field, the average Nusselt number increases with the increase of solid volume fraction.